2009
DOI: 10.1007/s12207-009-9046-3
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracies About the MMPI-2 Fake Bad Scale in the Reply by Ben-Porath, Greve, Bianchini, and Kaufman (2009)

Abstract: Based on a focused review and careful analysis of a large amount of published research, Butcher et al. (Psychol Inj and Law 1(3):191-209, 2008) concluded that the Fake Bad Scale (FBS) does not appear to be a sufficiently reliable or valid measure of the construct "faking bad". Butcher et al. (Psychol Inj and Law 1(3): [191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208][209] 2008) pointed out examples of errors in some of the most widely cited studies (including meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Rather than repeat our detailed responses to their initial review, we limit this comment to addressing new points Williams et al (2009) bring up and offer a succinct summary of the issues raised in this exchange. Williams et al (2009) begin their response with a case designed to illustrate the potential for harm from the use of the FBS. Their example, however, illustrates the potential for harm from misuse of the FBS.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than repeat our detailed responses to their initial review, we limit this comment to addressing new points Williams et al (2009) bring up and offer a succinct summary of the issues raised in this exchange. Williams et al (2009) begin their response with a case designed to illustrate the potential for harm from the use of the FBS. Their example, however, illustrates the potential for harm from misuse of the FBS.…”
mentioning
confidence: 99%
“…Moreover, this decision and the subsequent one made by an insurance company to deny befits to this patient, do not shed light on the scientific validity of the FBS as a measure of symptom over-reporting. Williams et al (2009) characterize the change of the label of FBS to "Symptom Validity" as "a very rare occurrence in the history of psychological measurement" (p. 186). They go on to describe this shift as "contrast [ing] sharply with the convention of supplementing the names and abbreviations given to the standard scales... with scale numbers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As for the FBS, which had been added to the MMPI-2 F family stable, the authors reviewed the exchange on its utility in the journal Psychological Injury and Law by Butcher and colleagues and Ben-Porath and colleagues (Butcher et al 2008;Gass et al 2010;Williams et al 2009;compared to Ben-Porath et al 2009. Butcher and colleagues and Ben-Porath and colleagues engaged in a heated debate over the value of the FBS scale.…”
Section: Practice Commentmentioning
confidence: 99%
“…The scale's addition did not come without controversy or criticism. In particular, it has been argued that it incorrectly classifies females and individuals with genuine medical problems as malingering (Butcher, 2010;Butcher, Arbisi, Atlis, & McNulty, 2003;Butcher, Gass, Cumella, Kally, & Williams, 2008;Dean et al, 2008;Gass, Williams, Cumella, Butcher, & Kally, 2010;Williams, Butcher, Gass, Cumella, & Kally, 2009). However, Ben-Porath et al (2009) demonstrated that when the recommended interpretive cutoff scores (FBS≥100T) were employed, few people with bona fide medical or neurological disorders were mistakenly recognized as noncredible responders.…”
Section: Mmpi-2 Over-reporting Indicatorsmentioning
confidence: 99%